2021
DOI: 10.1038/s41436-021-01264-0
|View full text |Cite
|
Sign up to set email alerts
|

Missense NAA20 variantsimpairing the NatB protein N-terminal acetyltransferase cause autosomal recessivedevelopmental delay, intellectual disability, and microcephaly

Abstract: Purpose N-terminal acetyltransferases modify proteins by adding an acetyl moiety to the first amino acid and are vital for protein and cell function. The NatB complex acetylates 20% of the human proteome and is composed of the catalytic subunit NAA20 and the auxiliary subunit NAA25. In five individuals with overlapping phenotypes, we identified recessive homozygous missense variants in NAA20. Methods Two different NAA20 variants were identified in affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Nt-acetylation catalyzed by the NATs is one of the most common protein modifications in eukaryotes, whose general role remains enigmatic. Mutations in the NATs can cause rare disorders, resulting in developmental delay, intellectual disability, and congenital heart defects (Cheng et al, 2018; Morrison et al, 2021; Muffels et al, 2021; Rope et al, 2011; Ward et al, 2021). The molecular framework and consequently the mechanistic basis for how the NATs manifest in cellular and organismal phenotypes remains however largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nt-acetylation catalyzed by the NATs is one of the most common protein modifications in eukaryotes, whose general role remains enigmatic. Mutations in the NATs can cause rare disorders, resulting in developmental delay, intellectual disability, and congenital heart defects (Cheng et al, 2018; Morrison et al, 2021; Muffels et al, 2021; Rope et al, 2011; Ward et al, 2021). The molecular framework and consequently the mechanistic basis for how the NATs manifest in cellular and organismal phenotypes remains however largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Given the prevalence of Nt-acetylation, NATs regulate a wide range of cellular processes, ranging from metabolism, cell proliferation and migration to differentiation and stress response (Aksnes et al, 2019). Dysregulation of Nt-acetylation can cause developmental disorders, by affecting brain and heart development, and contribute to cancer development (Aksnes et al, 2019; Cheng et al, 2018; Morrison et al, 2021; Muffels et al, 2021; Rope et al, 2011; Ward et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In yeast, it was shown that whereas N-α-acetylation by NatA seems to play a role in systemic adaptation control, modification by NatB seems rather to be important for protein folding [ 22 ]. Furthermore, depletion of NatB subunits to 30% of the wild-type level caused a 50% decrease in growth in Arabipopsis thaliana [ 23 ] and missense mutations in the catalytic domain NAA20 of human NatB were shown to cause autosomal recessive developmental delay, intellectual disability, and microcephaly, emphasizing the importance of NatB function for the cell [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Pathogenic biallelic variants in NAA20 were associated with a human disease characterized by developmental delay (DD), intellectual disability (ID) and microcephaly. 6 To date, only five patients from two families carrying two different variants in NAA20 have been described with limited clinical details. 6 We report two Italian siblings harboring biallelic novel variant in NAA20 along with clinical data of the previously published families, expanding the phenotype of this neurodevelopmental disorder.…”
Section: Introductionmentioning
confidence: 99%